Multipurpose diffractometer for in situ X‐ray crystallography of functional materials. Issue 3 (31st May 2021) - Gorfman, Semën; Spirito, David; Cohen, Netanela; Siffalovic, Peter; Nadazdy, Peter; Li, Youli
Abstract : The multipurpose four‐circle diffractometer in Tel Aviv University is described. The design, the beam quality (flux/divergence) and the application of the diffractometer for various tasks for in situ X‐ray crystallography of functional materials are demonstrated. Abstract : Laboratory X‐ray diffractometers play a crucial role in X‐ray crystallography and materials science. Such instruments still vastly outnumber synchrotron facilities and are responsible for most of the X‐ray characterization of materials around the world. The efforts to enhance the design and performance of in‐house X‐ray diffraction instruments benefit a broad research community. Here, the realization of a custom‐built multipurpose four‐circle diffractometer in the laboratory for X‐ray crystallography of functional materials at Tel Aviv University, Israel, is reported. The instrument is equipped with a microfocus Cu‐based X‐ray source, collimating X‐ray optics, four‐bounce monochromator, four‐circle goniometer, large (PILATUS3 R 1M) pixel area detector, analyser crystal and scintillating counter. It is suitable for a broad range of tasks in X‐ray crystallography/structure analysis and materials science. All the relevant X‐ray beam parameters (total flux, flux density, beam divergence, monochromaticity) are reported and several applications such as determination of the crystal orientation matrix and high‐resolution reciprocal‐space mapping are demonstrated. The diffractometer is suitable for measuring X‐ray diffraction in situ under an external electric field, as demonstrated by the measurement of electric‐field‐dependent rocking curves of a quartz single crystal. The diffractometer can be used as an independent research instrument, but also as a training platform and for preparation for synchrotron experiments.